The stellar 'Snake' – I. Whole structure and properties. Issue 1 (26th March 2022) - Wang, Fan; Tian, Haijun; Qiu, Dan; Xu, Qi; Fang, Min; Tian, Hao; Di, Li; Bird, Sarah A; Shi, Jianrong; Fu, Xiaoting; Liu, Gaochao; Cui, Sheng; et al.
ABSTRACT: To complement our previous discovery of the young snake-like structure in the solar neighbourhood and reveal the structure's full extent, we build two samples of stars within the Snake and its surrounding territory from Gaia Early Data Release 3 (EDR3). With the friends-of-friends algorithm, we identify 2694 and 9052 Snake member candidates from the two samples. 13 open clusters are embedded in these member candidates. By combining the spectroscopic data from multiple surveys, we investigate the comprehensive properties of the candidates and find that they are very likely to belong to one sizable structure, since most of the components are well bridged in their spatial distributions, and follow a single stellar population with an age of 30–40 Myr and solar metallicity. This sizable structure is best explained as hierarchically primordial, and probably formed from a filamentary giant molecular cloud with unique formation history in localized regions. To analyse the dynamics of the Snake, we divide the structure into four groups according to their tangential velocities. We detect anisotropic expansion rates of the groups along different axes, and find that the average expansion age ($\bar{τ }\simeq 33$ Myr) is highly consistent with the age of the Snake along the length of the structure ( X -direction). With over 10 000 member stars, the Snake is an ideal laboratory to study nearby coeval stellar formation, stellar physics, and environmental evolution over a large spatial extent.